An Analysis on Testing of Total Ozone Section through Ozone Monitoring Instrument; Some Methodologies: Investigating the Seasonal Variations of Total Ozone Section using Ozone Monitoring Instrument (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The goal of this work was to investigate the pattern of worldly changeability of the environmental Total ozone section (TOC) over Kathmandu, during the most recent 13 years of perceptions utilizing remote detecting determined information. For this examination, long haul TOC information got from the Ozone Monitoring Instrument (OMI) for the time of October 2004–April 2016 were utilized. The day by day, month to month, regular, and yearly varieties of TOC were investigated. During the entire investigation time frame, the most noteworthy estimation of TOC is observed to be 344 DU in March and the least estimation of TOC is 219 DU in December. The normal TOC determined during the entire examination time frame over Kathmandu is observed to be 268 DU. The pattern of TOC demonstrates a particular occasional example, with greatest in summer and least in winter season, explicitly high incentive in April or May and lower an incentive in December and January.